The history of the introduction of the giant river prawn, Macrobrachium cf. rosenbergii (Decapoda, Palaemonidae), in Brazil: new insights from molecular data - Iketani, Gabriel; Pimentel, Luciana; Silva-Oliveira, Glaúcia; Maciel, Cristiana; Valenti, Wagner Cotroni [UNESP]; Schneider, Horacio; Sampaio, Iracilda (Sociedade Brasileira de Genética, 2011)
The giant river prawn, Macrobrachium cf. rosenbergii, is one of the most cultivated freshwater prawns in the world and has been introduced into more than 40 countries. In some countries, this prawn is considered an invasive species that requires close monitoring. Recent changes in the taxonomy of this species (separation of M. rosenbergii and M. dacqueti) require a re-evaluation of introduced taxa. In this work, molecular analyses were used to determine which of these two species was introduced into Brazil and to establish the geographic origin of the introduced populations that have invaded Amazonian coastal waters. The species introduced into Brazil was M. dacqueti through two introduction events involving prawns originating from Vietnam and either Bangladesh or Thailand. These origins differ from historical reports of the introductions and underline the need to confirm the origin of other exotic populations around the world. The invading populations in Amazonia require monitoring not only because the biodiversity of this region may be affected by the introduction, but also because admixture of different native haplotypes can increase the genetic variability and the likelihood of persistence of the invading species in new habitats.
Keywords: Bioinvasion; exotic species; giant river prawn; Macrobrachium dacqueti; COI; 16S rRNA; Amazonia